2021
DOI: 10.1123/jsr.2019-0185
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 6 Weeks of Aquatic Exercise and Kinesio Taping in Patients With Chronic Nonspecific Low Back Pain

Abstract: Context: In many societies, although chronic low back pain (LBP) is a significant problem, there is no consensus on the optimal therapeutic intervention. Objective: To compare the impact of aquatic exercise (AE) and kinesio taping (KT) on the pain intensity and functional incapacity in women with chronic nonspecific LBP. Design: Randomized controlled trial. Setting: Outpatient clinic. Participants: Thirty-six women with chronic nonspecific LBP (mean [SD]: age = 50.69 [4.187] y) participated. Interventions: Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A relatively new treatment method for CLBP is Kinesio taping (KT), which is being widely used as a relatively novel band-aid method to reduce the pain of musculoskeletal disorders [4] . KT is an elastic bonding material containing high tensile capacity, which ensures the free movement of the application area without the need of drugs or chemicals [5–7] . Studies have shown that KT improves blood and lymph circulation, mitigates pain, adjusts joints, and relives muscle tension [8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively new treatment method for CLBP is Kinesio taping (KT), which is being widely used as a relatively novel band-aid method to reduce the pain of musculoskeletal disorders [4] . KT is an elastic bonding material containing high tensile capacity, which ensures the free movement of the application area without the need of drugs or chemicals [5–7] . Studies have shown that KT improves blood and lymph circulation, mitigates pain, adjusts joints, and relives muscle tension [8] …”
Section: Introductionmentioning
confidence: 99%
“…[4] KT is an elastic bonding material containing high tensile capacity, which ensures the free movement of the application area without the need of drugs or chemicals. [5][6][7] Studies have shown that KT improves blood and lymph circulation, mitigates pain, adjusts joints, and relives muscle tension. [8] One meta-analysis demonstrated that KT could improve pain and function in patients with CLBP compared with sham taping.…”
Section: Introductionmentioning
confidence: 99%
“…KT can be extended to 140% of the original length, providing a good range of motion in comparison with other types of tape. [ 7 , 8 ] Studies have shown that KT improves blood and lymph circulation, mitigates pain, adjusts joints, and relives muscle tension. Although the effect of KT on pain is unclear, KT may provide afferent stimuli that promote pain inhibition mechanisms and pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Two common treatments that are often employed for chronic LBP are transcutaneous electrical nerve stimulation and infrared ray thermal therapy (Jamison et al, 2019; Wong et al, 2012). Among the wide range of therapeutic exercises available, aquatic exercise is frequently recommended by physicians for chronic LBP, and it is becoming more and more popular as a treatment for this disorder (Alikhajeh et al, 2020; Zampogna et al, 2020). Therapeutic aquatic exercise refers to water-based treatments or exercise.…”
mentioning
confidence: 99%
“…Therapeutic aquatic exercise refers to water-based treatments or exercise. In view of water’s diverse characteristics, such as buoyancy pressure, density, heat capacity, and conductivity, it is a perfect setting for undertaking a workout program (Alikhajeh et al, 2020; Baena-Beato et al, 2013; Lahart & Metsios, 2018; Rivas Neira et al, 2017). In addition, compared to land-based exercise interventions, a person can benefit from the thermal impact of water in a shorter period of time.…”
mentioning
confidence: 99%